Surgery of the Chin - Nahai, Farzad R. (Facial Plastic Surgery, 2012)
With a clear understanding of the anatomy and thorough patient evaluation, a safe and effective surgical plan can be constructed. There are several options available to reduce or augment the chin, and often the choice is based on patient presentation and surgeon comfort and familiarity with a given procedure.
Keywords: chin implant; facial profile; genioplasty